The Allocation of Micro-grid Energy Storage System Considering Controlling Parameter - (:unkn) unknown (My University, 2018)
This research proposes a novel method of how to integrate controlling parameters, voltage and frequency, into to the energy storage system (ESS) allocation in a microgrid with renewable sources. The goal is to use the sensitivity analysis to find the most effective bus where the ESS should be in-stored to minimize the fluctuations both in terms of voltage and frequency. Indicators, such as SAIDI and SAIFI, are used to measure system reliability after the optimum size and location of ESS are determined.
Keywords: allocation; controlling parameter; energy storage system; sensitivity analysis